Chitosan‐Silica as a Cheap Carrier and Green Soft Ligand for Improved Ru‐catalyzed Hydroformylation. Issue 24 (17th November 2022) - Escobar‐Bedia, Francisco Javier; Martin‐Diaconescu, Vlad; Simonelli, Laura; Sabater, Maria J.; Concepción, Patricia
Abstract: Dodecacarbonyltriruthenium Ru3 (CO)12 has been immobilized onto a biopolymer (chitosan) supported on SiO2 (Ch@SiO2 ) to give Ru−Ch@SiO2 . Ch@SiO2 behaves as a soft, recoverable and bulky ligand allowing the stabilization of released Ru active species and preventing its irreversible reduction to Ru 0 . Under these conditions very high activity (TOF= 1086 h −1 ; TON=2749) and regioselectivity (n:iso=92 : 8) are obtained, surpassing that of the homogeneous Ru3 (CO)12 counterpart. Spectroscopic studies have shown that Ru3 (CO)12 transforms into a mononuclear Ru n+ (n=2, 3) di o try carbonyl species by interacting with the amido/amino groups of the biopolymer, being released into the reaction media whilst stabilized by the chitosan functional groups. The herein 0.5 Ru‐Ch@SiO2 catalyst can operate be operated under a semi‐continuous mode for at least 14 h without deactivation, representing providing a starting point in the search for a green catalyst with definitive industrial application in hydroformylations. In particular in the search for a heterogeneous catalyst away from the use of phosphines and their known drawbacks (i. e. tedious synthesis, facile oxidation of phosphor center, ..) as well as expensive Rh as active site. Abstract : Chitosan‐Silica for Ru‐catalyzed Hydroformylation : Ru3 (CO)12 has been immobilized onto a biopolymer (chitosan) supported on SiO2 (Ch@SiO2 ) to give Ru−Ch@SiO2 . Ch@SiO2 behaves as a soft, recoverable and bulky ligand allowing the stabilization of released mononuclear Ru active species and preventing its irreversible reduction to Ru 0 . Under these conditions very high activity (TOF= 1086 h −1 ; TON=2749) and regioselectivity (n:iso=92 : 8) can be achieved.